2007
DOI: 10.1159/000107520
|View full text |Cite
|
Sign up to set email alerts
|

FcγRII Activation Induces Cell Surface Ceramide Production which Participates in the Assembly of the Receptor Signaling Complex

Abstract: We studied an involvement of various cellular ceramide pools in signaling of immunoreceptor FcγII (FcγRII). The cell surface ceramide level was assessed by a technique based on binding of ceramide probes to intact cells. Total cellular ceramide was estimated by radioactive measurements. The activity of sphingomyelinases was measured by NBD-ceramide release while immunoprecipitation and immunoblotting were applied to analyze protein tyrosine phosphorylation. A complex pattern of protein phosphorylation was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Subsequent studies involving the imaging of immunolabeled ceramide show that many stimuli, including the activation of other immune cell receptors, induce the acid sphingomyelinase-mediated formation of ceramide-rich domains (Grassmé et al, 2002; Abdel Shakor et al, 2004; Korzeniowski et al, 2007). The activation of cluster of differentiation 40 (CD40), a member of the TNF-receptor superfamily found on antigen presenting cells, induced the formation of ceramide patches that largely colocalized with clustered CD40 and acid sphingomyelinase (Grassmé et al, 2002).…”
Section: Ceramide-rich Membrane Domains Induced By External Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies involving the imaging of immunolabeled ceramide show that many stimuli, including the activation of other immune cell receptors, induce the acid sphingomyelinase-mediated formation of ceramide-rich domains (Grassmé et al, 2002; Abdel Shakor et al, 2004; Korzeniowski et al, 2007). The activation of cluster of differentiation 40 (CD40), a member of the TNF-receptor superfamily found on antigen presenting cells, induced the formation of ceramide patches that largely colocalized with clustered CD40 and acid sphingomyelinase (Grassmé et al, 2002).…”
Section: Ceramide-rich Membrane Domains Induced By External Stimulimentioning
confidence: 99%
“…Similar to CD95, CD40 clustering, and subsequent signaling was inhibited by a loss of acid sphingomyelinase activity, neutralization of cell surface ceramide, and cholesterol depletion (Grassmé et al, 2002). Likewise, immunofluorescence imaging of ceramide showed the activation of Fc gamma receptor II (FcγRII), an immune cell receptor for IgG, induced acid sphingomyelinase activity at the cell surface and the formation of ceramide-rich membrane patches (Abdel Shakor et al, 2004; Korzeniowski et al, 2007). This ceramide production was required for the clustering of the crosslinked FcγRII, subsequent receptor phosphorylation, and signaling.…”
Section: Ceramide-rich Membrane Domains Induced By External Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Monolayers of ECs were fixed (1% PFA in TBS), then incubated with 2µg/mL anti-ceramide Ab (45-60 min, RT) and washed 3x with TBS as in [46]. Cell-bound Ab was released by 30 sec treatment with ice-cold 100 mM glycine, pH3.5, neutralized with 1M NaOH, and cell lysates spotted onto NC membrane using a dot-blot apparatus followed by incubation with anti-goat IgM HRP-conjugated.…”
Section: Methodsmentioning
confidence: 99%
“…Further ultrastructural studies performed on sheets of plasma membrane obtained by mechanical cleavage of cells revealed that PI(4,5)P 2 accumulated at the margins of raft conglomerates [43]. Such structures form during Fcc receptor II activation and accommodate the receptor and proteins of its signaling cascade [175,176]. At these particular locations, PI(4,5)P 2 may function in tethering the actin cytoskeleton to the plasma membrane (as proposed for T cell receptor) and govern internalization of particles.…”
Section: Pip5kica and Icc Bind Talin At Focal Contactsmentioning
confidence: 99%